A Need for Consistency in Behavioral Phenotyping for ASD: Analysis of the Valproic Acid Model. (20th March 2021) - Larner, Olivia; Roberts, Jane; Twiss, Jeffery; Freeman, Linnea
Abstract : Autism spectrum disorder (ASD) is a highly prevalent and impairing neurodevelopmental disorder that affects 1 : 54 persons. Over the last several decades, the reported incidence of ASD in the US has increased potentially due to increased awareness and improved diagnostic measurement. Although ASD prevalence is increasing, the etiology of ASD remains relatively unknown. To better understand the neurological basis of ASD, rodent models of ASD have been developed for research. Currently, there is not a standardized set of behavioral tests to quantify ASD-like behavior in rodents. The goal of this review is to present an overview of the methodologies used to analyze ASD-like behaviors in rodents, focusing on the valproic acid (VPA) model, and illustrate inconsistencies between different approaches. Despite that the in utero VPA rodent model for ASD is widely used and extensively characterized, behaviors vary substantially between different researchers. Moving forward, consistency in behavioral method analytics would benefit progress in evaluating interventions for all models of ASD and help to uncover unique qualities underlying mechanisms causing ASD signs and symptoms.